EMPIRICAL EVIDENCE OF THE ROLE OF ACCOUNTING POLICY ON BOND RATING TO FINANCIAL COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Steacy Chaterine Tan (Media Riset Akuntansi, Auditing & Informasi, 2018)
The objective of the empirical study is to examine the effect of leverage, liquidity, profitability and accounting policies on bond rating. The sample of this empirical study is financial companies that listed in Indonesia Stock Exchange during 2012-2016. The results of this empirical study shows that leverage affects negatively on bonds rating. While, liquidity, profitability, and accounting policy affect positively on bonds rating.